Neuropeptide Y receptors: how to get subtype selectivity - Pedragosa Badia, Xavier; Stichel, Jan; Beck-Sickinger, Annette G. (Frontiers in Endocrinology, 2013)
The neuropeptide Y system is a multireceptor/multiligand system consisting of four receptors in humans (hY1, hY2, hY4, hY5) and three agonists (NPY, PYY, PP) that activate these receptors with different potency. The relevance of this system in diseases like obesity or cancer, and the different role that each receptor plays influencing different biological processes makes this system suitable for the design of subtype selectivity studies. In this review we focus on the latest findings within the NPY system, we summarize recent mutagenesis studies, structure activity relationship studies, receptor chimera and selective ligands focusing also on the binding mode of the native agonists.